Impacts of climate change on chronic respiratory health in Ethiopia: a systematic review and meta-analysis - Andualem, Zewudu; Alemu, Ayenew Takele; Geddif, Azeb; Kassie, Genet Gedamu; Mitiku, Kalkidan Worku; Belay, Mahider Awoke; Simegn, Mulat Belay; Chanie, Samuel Dagne; Tilahun, Werkneh Melkie; Menber, Yonatan; Wasihun, Yosef; Gebreegziabher, Zenebe Abebe (Frontiers in Climate, 2025)
IntroductionClimate change presents profound public health challenges, particularly in low-income countries like Ethiopia. Chronic respiratory diseases and chronic respiratory symptoms, are exacerbated by environmental factors such as air pollution, extreme temperatures, and occupational exposure. Despite its vulnerability, Ethiopia lacks comprehensive data on impacts of climate change on chronic respiratory health, limiting effective policy and intervention strategies. Therefore, the aims of this study to assess the impact of climate change on chronic respiratory health in Ethiopia.MethodsA systematic review and meta-analysis were conducted using Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Studies published between 2015 and 2024 were retrieved from PubMed, Embase, Google Scholar, and institutional repositories. Eligible studies focused on chronic respiratory diseases and chronic respiratory symptoms in Ethiopia and employed observational designs. Data extraction followed Joanna Briggs Institute protocols, and risk of bias was assessed using Hoy et al.’s checklist. Statistical analyses were performed in STATA 14, including pooled prevalence estimation using a random-effects model, subgroup analyses by region and study design, and publication bias assessment using Egger’s test and funnel plots.ResultsA total of 21 studies with 10,785 participants were included, the pooled prevalence of chronic respiratory health was 39% (95% CI: 31–48%). The most common symptoms were cough, phlegm, wheezing, and shortness of breath. Air pollution, particularly particulate matter (PM2.5 and PM10), temperature, and altitude were reported as a significant contributor. Subgroup analysis revealed the highest prevalence in Oromia (61, 95% CI: 58–64%) and the lowest in the Southern Nations, Nationalities and People Region (23, 95% CI: 13–33%). Study design influenced prevalence estimates, with cross-sectional studies reporting higher rates (46%) than case–control studies (14%). Significant heterogeneity (I2 = 99%, p < 0.001) was observed across studies.ConclusionThe findings highlight a substantial burden of chronic respiratory health in Ethiopia, resulting from climatic, environmental, and occupational exposures. Decreasing biomass fuel use, enhancing air quality, and incorporating climate adaptation measures into public health policy are key interventions.